Determinants of tax administration efficiency and the moderating role of leadership among tax employees in Yemen - Al-Harethi, Abobakr Ramadhan (2024)
The inefficiency of tax administration is a continuous serious concern globally. However, empirical research on determinants of the efficiency of tax administration in Yemen is still scarce. The major purpose of this study was to investigate the determinants of tax administration efficiency in Yemen. It aimed to empirically investigate the relationships between motivation, attitude, autonomy, job satisfaction, emotional intelligence, information communications and technology (ICT), training and tax administration efficiency. As a new contribution to tax administration efficiency knowledge, the moderating effect of leadership on the relationship between tax administration efficiency and its determinants was also examined. The underlying theory of this study is the Resource-based View (RBV), which is supported by Social Exchange Theory (SET). Questionnaires were distributed to 505 employees of the Yemeni Tax Authority (YTA) from six governorates. From there, off which 325 responses were received, with a response rate of 64.4%. However, only 306 questionnaires were suitable for analysis. The data was analysed using SPSS23 and SmartPLS 3. The analysis shows positive relationships between motivation, attitude, job satisfaction, emotional intelligence, ICT and training on tax administration efficiency. However, there is no relationship between autonomy and tax administration efficiency. In addition, the moderating effect of leadership was found to be significant in the relationship between autonomy, job satisfaction and tax administration efficiency. The study indicated that the moderating role of leadership was insignificant in the influence of motivation, attitude, emotional intelligence, ICT and training on tax administration efficiency. This study is indirectly beneficial to different groups, including YTA, tax practitioners, students and other stakeholders from tax revenue agencies. Its conclusions are particularly relevant to the YTA's goal of improving tax knowledge, efficiency of tax administration and increasing revenue by reducing tax non-compliance.